Probable RBD Associates with the Development of RLS in Parkinson’s Disease: A Cross-Sectional Study - Yewei Qu; Lu Zhang; Dongfang Shen; Wangzikang Zhang; Mingsha Zhang; Yujun Pan (Behavioural Neurology)
Objectives. We aimed to investigate the prevalence of restless leg syndrome (RLS) and exploring the contributing factors that affect the development of RLS in Parkinson’s disease (PD) patients. Methods. A cross-sectional study was conducted consisting of 178 consecutive PD patients from our hospital between October 2015 and August 2016. We divided the participants into two groups, which were PD with RLS and PD with non-RLS. Then, we recorded their demographics and clinical data to draw a comparison between PD with RLS and PD with non-RLS. Results. 23 (12.92%) were diagnosed with RLS among all the enrolled PD patients. Unified Parkinson’s Disease Rating Scale III (UPDRS III) and Hamilton Depression Scale (HAMD) scores, probable rapid eye movement sleep behavior disorder (PRBD), and daily levodopa equivalent dose (LED) in the PD with the RLS group were significantly different from those in the PD with the non-RLS group. Daily LED and the scores of UPDRS III and HAMD in PD patients with RLS were all higher than those in PD patients with non-RLS. PRBD, daily LED, and HAMD scores were significantly independent factors contributing to the development of RLS (OR=4.678, 95% CI 1.372~15.944, P=0.014; OR=1.003, 95% CI 1.001~1.005, P=0.019; OR=1.094, 95% CI 1.002~1.193, P=0.045). The severity of RLS was positively correlated with the duration of PD and daily LED (r=0.438, P=0.036; r=0.637, P=0.001). Conclusion. PRBD existence, daily LED, and HAMD scores are independent factors for developing RLS in PD patients. PRBD existence is firstly proposed as an independent factor in developing RLS among PD patients. RLS severity in PD patients are positively associated with the duration of PD and daily LED.